Penta-Helix Model of Merdeka Kurikulum to Address Learning Loss at SMA Al-Islam 1 Surakarta - Mustofa, Rochman Hadi; Ramadhan, Muhammad Tanzilal; Buana, Dewangga Satria; Karima, Mutiara; Narmanditya, Bagus Shandy (Universitas Muhammadiyah Surakarta, 2024)
The learning loss that emerged after online learning during the COVID-19 pandemic has resulted in low motivation and slow psychological development among students. This study aims to investigate the implementation of strategies to address learning loss through the implementation of the Merdeka Curriculum at SMA Al-Islam 1 Surakarta, a